Oppositely Charged Ti3C2Tx MXene Membranes with 2D Nanofluidic Channels for Osmotic Energy Harvesting. (18th February 2020) - Ding, Li; Xiao, Dan; Lu, Zong; Deng, Junjie; Wei, Yanying; Caro, Jürgen; Wang, Haihui
Abstract: Membrane‐based reverse electrodialysis (RED) is considered as the most promising technique to harvest osmotic energy. However, the traditional membranes are limited by high internal resistance and low efficiency, resulting in undesirable power densities. Herein, we report the combination of oppositely charged Ti3 C2 T x MXene membranes (MXMs) with confined 2D nanofluidic channels as high‐performance osmotic power generators. The negatively or positively charged 2D MXene nanochannels exhibit typical surface‐charge‐governed ion transport and show excellent cation or anion selectivity. By mixing the artificial sea water (0.5 m NaCl) and river water (0.01 m NaCl), we obtain a maximum power density of ca. 4.6 Wm −2, higher than most of the state‐of‐the‐art membrane‐based osmotic power generators, and very close to the commercialization benchmark (5 Wm −2 ). Through connecting ten tandem MXM‐RED stacks, the output voltage can reach up 1.66 V, which can directly power the electronic devices. Abstract : Fahrt ins Blaue : Osmotische Energie, auch bekannt als „blaue Energie", wird durch Einfangen der Energie des Salzgehaltsgradienten zwischen Meerwasser und Süßwasser gewonnen. Negativ und positiv geladene lamellare MXen‐Membranen mit eingeschlossenen 2D‐Nanofluidik‐Kanälen ermöglichen die hoch effiziente Gewinnung osmotischer Energie bei einer Leistungsdichte von 4.6 W m −2 durch Mischen von künstlichem Meerwasser und Flusswasser.